TECHNOLOGY FOR OBTAINING BIMETALLIC SHAPING PARTS OF DIE TOOLING USING METHOD OF HIGH-SPEED HOT EXTRUSION - I. V. Kachanov; M. V. Kudin; S. A. Lenkevich (Наука и техника)
Processes of high-speed shaping changes and especially high-speed hot extrusion create efficient conditions for treatment of weakly plastic and poorly deformable materials which are widely used in tool making facilities. Due to the fact that high-speed stamping provides accurate billets with increased mechanical properties, it can be used as a technological process for manufacturing shaping parts of die tooling parts operating which are subjected to increased loads and wear.The purpose of the paper is to carry out experimental investigations on the possibility to obtain a bimetallic tool where structural steel is considered as a basis of the tool and a working cavity is made of high-alloyed tool steel with its saving up to 90 %. A scheme of loading and geometry of conjugated surfaces of the composite billet have been developed in the paper. Technology for obtaining bimetallic shaping parts of die tooling with deformation at speed of vR = 40-50 m/s and composite billet temperature of T = 1150 °C has been experimentally tested with formation of a compound due to plastic flow of two billet parts on contact surface with removal of surface oxide films.Microstructures of the bimetallic compounds obtained with the help of high-speed hot extrusion method for compositions of structural and high-alloy steels have been investigated and their high quality has been proved during the investigations. Dependences of micro-hardness distribution have been established outbound two- steel contact plane in the zone of connection that are characterized by a minimum micro-hardness value in the connection joint. Availability of more plastic zone in the contact plane contributes to reduction of residual stresses due to their relaxation in this zone and higher joint strength.